Synthesis of particle for the application of pulmonary drug delivery. - Ng, Zhihan. (2009)
The effects of the particle shape and size on the particles’ flow properties are being examined in this study. To achieve particles that are of different shape and sizes, four different experiments, which include crystallization and precipitation, are being conducted. The experiments used different surfactants and reagents to control the physical properties of the synthesized particles, which cannot be achieved through spray drying and micronization. The Scanning Electron Microscopy (SEM) helped analyzes the physical properties, including the shape, average size and morphology, of the particles synthesized. By obtaining the average size and shape of the particles, the equivalent diameter of the particles can be determined. Coupled with the particle density, the aerodynamic diameters of particles can be determined. Using different concentrations of Poly-(styrene-alt-maleic acid) (PSMA), to synthesize calcium oxalate particles, it was believed that increasing the concentration of PSMA in the final solution will reduce the size of the particles achieved due to the nucleation and growth theory. In addition, by altering the pH of the final solution, a substantial control of particles’ shape can be achieved. Unfortunately, it has not been possible to synthesize the particles desired required for the study and the flow properties of the particles are not analyzed. The surfactant Poly(sodium 4-styrene sulfonate) (PSS) was used to control the synthesis of hydroxyapatite (HA) particles and it has been accepted that the size and surface morphology of the particles can be altered with varying concentration of PSS and urea. It was also observed in this study that Ostwald ripening also plays a part in controlling the surface morphology of the particles. Two particles synthesized using the same concentration of PSS and urea, with different aging time meets the requirements for the study and these particles return one of the best flow properties amongst the group of particles synthesized. This has been attributed to the surface morphology of the different particles, which reduces point charge and particle interactions. Aragonite particles that were synthesized using different concentrations of reagents also showed that particles’ size and shape can be controlled during synthesis. The particles synthesized changes from cubic particles to particles that resembled rods that were bent. It was observed that the rod-like particles give contrasting flow property results, with a low angle of slide but high Carr’s compressibility index whereas cubic particles are observed to be very cohesive and does not possess good flow properties. It was also observed that the aerodynamic diameters of cubic particles, in the size range, can be approximated by their geometric size. Lastly, CTAB was used as a surfactant to synthesize calcium carbonate particles where the use of different concentrations of CTAB and temperature will alter the shape and size of the particles being synthesized. Several of the particles synthesized meet the requirements of this study and their flow properties are being assessed and compared with the rest of the particles synthesized. It was observed from the flow properties that the HA particles synthesized in this study gives the best flowability and aerodynamic diameter required of a good pulmonary drug.